MANAJEMEN LABA DAN PERENCANAAN PAJAK SEBAGAI SUMBER LARGE POSITIVE BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA - Liean Winata Merrysa; Nurul Aisyah Rachmawati (Universitas Bunda Mulia, 2018)
This study replicates Blaylocket al. (2012). Through this research, the writer wanted to analyze the influence of earnings management and tax planning as source of Large Positive Book-Tax Differences (LPBTD) to earnings persistence. This research uses panel data of manufacturing companies listed on Indonesia Stock Exchange for the period of research year 2012-2013. The data is analyzed with Pooled Least Square. Unfortunately, the authors can not prove that earnings management as a source of LPBTD can weaken earnings persistence. The result of earnings persistence estimation is exactly the opposite. This condition may occur because the action of earnings management by managers is viewed in terms of efficiency contracting perspective. In addition, the authors also can not prove that tax planning as a source of LPBTD strengthens the profit persistence. According to Blaylock et al. (2012), this happens because the measurement of cash effective tax rate can not be reviewed only with period of 5 (five) years.Keywords:Persistensi profit, profit management, tax planning, Large positive book-tax differences